2020
DOI: 10.3390/cells9061445
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor β (FRβ) Expression in Tissue-Resident and Tumor-Associated Macrophages Associates with and Depends on the Expression of PU.1

Abstract: As macrophages exhibit a huge functional plasticity under homeostasis and pathological conditions, they have become a therapeutic target for chronic inflammatory diseases. Hence, the identification of macrophage subset-specific markers is a requisite for the development of macrophage-directed therapeutic interventions. In this regard, the macrophage-specific Folate Receptor β (FRβ, encoded by the FOLR2 gene) has been already validated as a target for molecular delivery in cancer as well as in macrophage-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 95 publications
(142 reference statements)
1
27
0
Order By: Relevance
“…3e). Tissue resident LYVE1 + macrophages have been previously associated with angiogenesis 19,21 , arterial stiffness 27 and anti-inflammatory phenotypes 23 . In agreement, we found that endometriosis Mφ1-LYVE1 upregulate tolerogenic (IL10, VSIG4, RGS1, EGFL7) and angiogenesisrelated genes (THBS1, HBEGF, PDGFB, PDGFC, IGF1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3e). Tissue resident LYVE1 + macrophages have been previously associated with angiogenesis 19,21 , arterial stiffness 27 and anti-inflammatory phenotypes 23 . In agreement, we found that endometriosis Mφ1-LYVE1 upregulate tolerogenic (IL10, VSIG4, RGS1, EGFL7) and angiogenesisrelated genes (THBS1, HBEGF, PDGFB, PDGFC, IGF1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified five Mf subpopulations, of which Mf1-LYVE1 and Mf3-APOE were previously identified by single cell analysis in other systems 8,21,22 . Tissue-resident macrophage subpopulations (Mf1-LYVE1, Mf2-peritoneal and Mf3-APOE) are distinguished by their expression of FOLR2-a gene associated with embryonic-derived tissue resident macrophages 19,23 . Mf2-peritoneal subpopulation is exclusive to peritoneal tissue and express ICAM2, a known marker for peritoneal macrophage 24 .…”
Section: Active Vascular Remodeling and Immune Cell-trafficking Prevail In Endometriosis Peritoneal Lesionsmentioning
confidence: 99%
“…3e). Tissue resident LYVE1 + macrophages have been previously associated with angiogenesis 19,21 , arterial stiffness 27 and anti-inflammatory phenotypes 23 . In agreement, we found that endometriosis Mf1-LYVE1 upregulate tolerogenic (IL10, VSIG4, RGS1, EGFL7) and angiogenesis-related genes (THBS1, HBEGF, PDGFB, PDGFC, IGF1) (Fig.…”
Section: Active Vascular Remodeling and Immune Cell-trafficking Prevail In Endometriosis Peritoneal Lesionsmentioning
confidence: 99%
“…To that end, we first evaluated whether LXR is involved in the macrophage polarizing ability of tumor-conditioned fluids, and specifically of ascitic fluids from tumors of various origins (Figure 7A). The M-CSF-induced expression of two functionally relevant markers of tumor-associated macrophages, IGF-1 (66, 67) and FOLR2 (63,68), was prevented in the presence of the LXR agonist GW3965 (Figure 7B). Moreover, the upregulation of both genes in the presence of ascitic fluids was also impaired by the LXR agonist (Figure 7B), implying that the polarizing ability of tumor-conditioned media is dependent on LXR activity.…”
Section: Lxr Inhibition Modulates the Gm-csf-dependent Macrophage Difmentioning
confidence: 99%